Control of Deoxyribonucleic Acid and Ribonucleic Acid Synthesis in Pyrimidine-Limited Escherichia coli - Dennis, Patrick P. (1970)
The effects of pyrimidine limitation on chromosome replication and the control of ribosomal and transfer ribonucleic acid syntheses were investigated. Chromosome replication was studied by autoradiography of (3)H-thymine pulse-labeled cells. Pyrimidine limitation did not affect the fraction of cells incorporating radioactive thymine during a short pulse, indicating that when growth is limited by the supply of pyrimidine, the time required for chromosome duplication increases in proportion to the time required for cell duplication. Control of ribosomal RNA and transfer RNA syntheses was examined by chromatographing cell extracts on methylated albumin kieselguhr columns. When growth was controlled by carbon-nitrogen limitation, the ratio of tRNA to total RNA remained roughly constant at growth rates above 0.5 doublings per hour. During pyrimidine limitation, however, the control of rRNA synthesis was apparently dissociated from the control of tRNA synthesis: the ratio of tRNA to total RNA increased as the growth rate decreased.